Solid Waste Characterization and Recycling Potential in University of Phayao, Northern Thailand - Sangkham, Sarawut; Sangsrichan, Chaiwat (Naresuan University Journal: Science and Technology (NUJST), 2020)
The objective of this study is to determine solid waste generation and waste composition, and its physical and chemical characteristics. Surveys were conducted in both 2018 and 2019, the dry seasons, to evaluate the types of composition, its quantity, its physical and chemical characteristics, and solid waste generation. The sampling was collected on weekdays and was analyzed using the ASTM standard methods. The total solid waste collected in the university area averaged to 750 kg/day. The solid waste generation rate was approximately 0.32 kg/capita/day, with food wastes representing the largest portion of waste at 33.65%, followed by plastic and papers at 32.96% and 18.82%, respectively. The results show that in the physical characteristics, combustibles were the highest with 92.71%, followed by non-combustibles and other wastes were 3.61% and 3.68%, respectively. The results show that the average chemical characteristics: moisture content, total solids, volatile solid, carbon fixed, hydrogen, and ash content from the solid waste in this study was 21.67%, 78.33%, 47.94%, 26.63%, 31.96%, and 38.34%, respectively. This paper focused on determining the physical composition and chemical characteristics of solid waste. These characteristics proved that the high amount of combustibles in University of Phayao can be potentially used as solid waste through waste compacting refuse-derived fuel (RDF) which would be an appropriate option of solid waste management in University of Phayao. Hence, to achieve sustainable waste management, it is essential to start formulating environmental policies continuously together with campaigns raising awareness among the students and staff within the university, such as solid waste separation and reduction of single-use plastic bags. Also, consumers should receive reward points for not accepting plastic bags and there should be a recyclable solid waste bank.